Penerapan Asas Equality Before The Law Dalam Pembuatan Akta Keterangan Waris Bagi Etnis Tionghoa di Indonesia - Kussoy, Nathasya Fransiska Nancy; Priyanto, I Made Dedy (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
The writing of this article is to find out the application of the principle of equality before the law in according to the Regulation Of The Minister Of State For Agrarian/Head Of The National Land Agency number 3 of 1997 concerning The Implementation Of Government Regulation number 24 of 1997 concerning Land Registration Article 111 paragraph 1 letter (c) especially with regard to distribution community groups related to the processing of inheritance certificates after the enactment of Law number 40 of 2008 concerning the Elimintation of Racial and Ethnic Discrimination. To answer this, the author uses a normative legal research, namely a research method that places positive legal norms as the object of study, in order to support this research, form the results of study that the distribution of community groups related to the management of inheritance certificates does not apply the principle of equality before the law because in the processing of the certificate of inheritance has different requirements for Indonesian citizens (native) and Indonesian citizens of Chinese descent, for native Indonesian citizens, the processing of an inheritance certificate can be done through the local urban village office and does not require a fee, while the citizens Indonesians of Chinese descent can make arrangements through a Notary which obviously requires a fee.